Reviews of Environmental Contamination and Toxicology Volume 224 - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews,, 2013)
CONTENTS Foreword Preface Microbial Interactions in the Arsenic Cycle: Adoptive Strategies, and Applications in Environmental Management Umesh Praveen Dhuldhaj, Ishwar Chand Yadav, Surendra Singh and Naveen Kumar Sharma Chemical Behavior of Phthalates under Abiotic Conditions in Landfills Jingyu Huang, Philip N. Nkrumah, Yi Li and Gloria Appiah-Sefah The Environmental and Human Effects of Ptaquiloside-induced Enzootic Bovine Haematuria: a Tumorous Disease of Cattle Rinku Sharma, Tej K. Bhat and Om P. Sharma Methods for Deriving Pesticide Aquatic Life Criteria for Sediments Tessa L. Fojut, Martice E. Vasquez, Anita H. Poulsen and Ronald S. Tjeerdema Index